Transforming construction waste into eco-friendly foundations for lightweight housing: case study - Hasan, Ahmed M.; Ibrahim, Hawkar H.; Hummadi, Rizgar A. (Zanco Journal of Pure and Applied Sciences, 2026)
Construction activities generate large quantities of waste materials, creating significant challenges for waste management and environmental sustainability. This study investigates the feasibility of reusing coarse-grained construction waste deposited in a landfill as a foundation for lightweight residential buildings. To assess its long-term engineering performance, in-situ plate load tests were carried out on landfill material that had been in place for approximately ten years, as well as on the underlying natural coarse- and fine-grained soils after removal of the landfill. The tests were performed under three ground conditions: natural moisture content, submerged conditions after three days of inundation, and full landfill flooding achieved by filling a surrounding trench with water once the applied stress reached 200 kPa and maintaining saturation for 24 hours. The results indicated that although the landfill exhibited a collapse at 200 kPa following saturation, the settlements recorded under both dry and submerged conditions remained within acceptable limits for lightweight structures.